Editorial quality associated with the impact index of institutional scientific journals in the Tacna region - Salazar Paco, Olga Elizabeth (2022)
The study aimed to determine the association between editorial quality and impact index of institutional scientific journals of the Tacna region in the period 2018 - 2019. It was a documentary, cross-sectional, retrospective and correlational research. The study population consisted of 32 issues corresponding to eight local scientific journals. The instruments used were documentary observation, one referred to the verification of the editorial quality characteristics of the Latindex Catalog 2.0 and the second to the recording of the impact index of the issues evaluated. Regarding the results, after the application of Pearson's Chi-square test (p= 0.892) Yates 1.000 continuity correction>α= 0.05; therefore, there was no association between the study variables. Likewise, it was found that only 29.1% of the issues of the scientific journals met the editorial quality criteria Catalog 2.0 Latindex, the least covered being the group of characteristics of online journals, management and editorial policy, and presentation. In relation to the impact index, only 59.4% of the issues reached a numerical value different from zero, the rest did not obtain citations in the period evaluated. Finally, at the global level for the year 2020, the journals with the highest impact index in Tacna were: Iberoamerican Business Journal, Revista Médica Basadrina and Neumann Business Review.